Kesiapan Implementasi Badan Hukum Pendidikan (BHP) - Nurbayani, Etty; Wahdatunnisa, Wahdatunnisa (LP2M IAIN Samarinda, 2012)
A change in format of state university to education legal entity allows the existence of autonomous. Thus, a rector is more creative and no longer bounded by structure and bureaucratic mechanism. The autonomous in academic, finance, administration, personnel, etc., followed by a possible optimal accountability where every year the rector must give a responsibility report to senate, assembly of guardian trustful, external auditor, public accountant, and Finance Minister also Minister of National Education.